2015
DOI: 10.1002/cpdd.201
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability, safety, and pharmacokinetics of the novel cathepsin A inhibitor SAR164653 in healthy subjects

Abstract: Cathepsin A (CathA) is a lysosomal protein where it forms a stable complex with neuraminidase and ß-galactosidase. CathA also has enzymatic activity and is involved in the degradation of many peptides. CathA was recently discovered as a target for heart failure, fostering the development of CathA inhibitors with SAR164653 as a frontrunner. The first-in-man study investigated single oral doses from 20 to 800 mg of SAR164653 followed by repeat dose studies at doses up to 800 mg in healthy young and elderly subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Figure 5 shows the effects of CatA inhibitor ebelactone B (Ebel) and a novel, more selective CatA inhibitor, designated as compound 2a, SAR1, or SAR164653151617, on the previously described synergistic effects by L-ala, S P prodrugs in hiPSC-CM syncytia on FP rate and IMP amplitude measured in the CardioECR platform. To maximize the effects of CatA inhibitors, hiPSC-CM syncytia were pre-incubated with these reagents for 30 minutes prior to a second addition at time = 0, alone or combined with other test agents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5 shows the effects of CatA inhibitor ebelactone B (Ebel) and a novel, more selective CatA inhibitor, designated as compound 2a, SAR1, or SAR164653151617, on the previously described synergistic effects by L-ala, S P prodrugs in hiPSC-CM syncytia on FP rate and IMP amplitude measured in the CardioECR platform. To maximize the effects of CatA inhibitors, hiPSC-CM syncytia were pre-incubated with these reagents for 30 minutes prior to a second addition at time = 0, alone or combined with other test agents.…”
Section: Resultsmentioning
confidence: 99%
“…Ebelactone B was purchased from Enzo Life Sciences, Inc. (Farmingdale, NY, USA) and Santa Cruz Biotechnology, Inc. (Dallas, TX, USA). CatA inhibitor SAR164653 (also known as compound 2a, or SAR1)151617 was synthesized in house for research purposes.…”
Section: Methodsmentioning
confidence: 99%
“…The protective role of the enzyme for galactosidase and neuraminidase is a structural function of the enzyme: mice with catalytic serine-to-alanine mutation have normal levels of β-galactosidase and neuraminidase ( Seyrantepe et al, 2008 ). CTSA inhibitors have been tested in humans ( Tillner et al, 2016 ), and CTSA is a therapeutic target for the treatment of cardiovascular diseases ( Schreuder et al, 2014 ; Petrera et al, 2016 ). Thus, it would be interesting to test CTSA inhibitors in Niemann-Pick models.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it would be interesting to test CTSA inhibitors in Niemann-Pick models. PPT1 is also a lysosomal enzyme ( Lu et al, 2002 ) and the dysregulation of this enzyme causes a lysosomal storage and neurodegenerative disorder; infantile neuronal ceroid lipofuscinosis ( Tillner et al, 2016 ). This enzyme removes palmitoyl modifications from proteins that are being degraded in the lysosome.…”
Section: Discussionmentioning
confidence: 99%
“…In as mall phase Is afety trial, compound 443 showed af avorable safety profile with good tolerability and PK properties. [172] However,S anofid iscontinued further development of 443 for the treatment of heart failure in 2013, but continued to study it for the treatmento fpulmonary hypertension. [173] SAR164653 (443)i se xploited as am echanistic probe in physiological experiments in whichs mall-molecule Cat Ai nhibitors are studied.…”
Section: Sar164653mentioning
confidence: 99%